Analisa Pengangguran Di Provinsi Kalimantan Tengah - Sri Cici Afrida Cahyati; Kristina Thai; Lisa Carline; Hotni Mutiara; Elvina Syahara (Trending: Jurnal Manajemen dan Ekonomi, 2023)
Unemployment is a condition that results from a person's inability to get the job they want and need. From this we can conclude that this is a situation where someone who is classified as working but has not found a job and is looking for or trying to work, that is why it is necessary to analyze an unemployment in order to find out its causes and effects, here we use the observational analysis method which data we collect Get it from the Central Statistics Agency which can be read by the whole community.